A heterogeneous interface on NiS@Ni3S2/NiMoO4 heterostructures for efficient urea electrolysis. Issue 35 (21st August 2020) - Sha, Linna; Liu, Tianfu; Ye, Ke; Zhu, Kai; Yan, Jun; Yin, Jinling; Wang, Guiling; Cao, Dianxue
Abstract : A NiS@Ni3 S2 /NiMoO4 heterostructure serves as a bifunctional catalyst for highly efficient and durable overall urea electrolysis. Abstract : Urea electrolysis is an appealing energy conversion technology to produce hydrogen (H2 ) and alleviate the problem of urea-rich wastewater treatment concurrently. In particular, electrocatalytic performance can be dramatically enhanced by rationally modulating the surface charge distribution with a well-tuned heterostructure. Herein, a heterostructure is constructed by NiMoO4 nanosheets grown on an interior hollow NiS@Ni3 S2 nanorods framework (NiS@Ni3 S2 /NiMoO4 ). Density functional theory (DFT) calculations demonstrate that the formed heterojunction structure leads to a tailored surface charge state of NiMoO4, with oxygen as the nucleophilic region and molybdenum as the electrophilic region, which facilitates the decomposition of urea molecules and thus significantly improves hydrogen evolution. As expected, the assembled NiS@Ni3 S2 /NiMoO4 system substantially expedites urea electrolysis activity with a cell voltage of 1.40 V at 10 mA cm −2, which is 200 mV less than the voltage of an overall water splitting system.